Queuing management towards achieving customer satisfaction in three-star hotel segment in Malaysia / Mohd Zool Fadli Ibrahim - Ibrahim, Mohd Zool Fadli (2010)
In an intensely competitive world pressure, expectation of need to accomplish more in less time is likely the main priority of most hotels customers. Customer waiting time for service typically represents the first direct interaction between customers and most service delivery processes in hotel operations. Today, many people are basically surprise to discover a queue, especially when the service itself is not overloaded. Customer feels that they are wasting their time seems that time nowadays is consider as valuable. The purpose of this study is to present the role of psychology of queuing in mediating queuing management toward customer satisfaction. Queuing management dimension consist of multi channel services and installation of distraction, since both are appropriate method that can be practiced in hotel. The dimensions in psychology of queuing include certainty, fairness and value of services. To measure customer satisfaction, the behavioral intention will be use. All the variables is adapt from previous research which is conducted in different settings, in different location. This research involves a distribution set of questionnaire with customer selected randomly based on their experience stayed at three star hotels in Kuala Lumpur. Empirical data are analyzed using structural equation models. The findings of this study show that there is a significant relationship between queuing management and customer satisfaction. However, the relationship is varies among dimensions. Psychology of queuing however has a small mediating influence on the relationship of queuing management and customer satisfaction. Implication of this study is present in two forms, managerial and theoretical. The limitations of this study are based on the local setting, thus the performance of current situation.